THE EPISTEMOLOGICAL CHALLENGES AND PRACTICAL FOR RACISM COPING IN THE SCHOOL - Marques, Eugenia Portela Siqueira (2020)
This article presents the methodological procedures and the results of the survey "Public Policies for the Education of Ethnic-racial Relations: the Possibilities Open by Law n 10.639/03 in the state public schools of Mato Grosso do Sul". The research was conducted in partnership with the Center of Diversity of the State Department of Education and the Nucleus of Afro-Brazilian Studies of the Universidade Federal da Grande Dourados, and presents the epistemological and practical challenges for curricular decolonization and tackling racism in the school environment. The process of implementing the National Curriculum Guidelines for the Education of Ethnic-racial Relations and for the Teaching of the History and Afro-CultureBrazilian and African challenges school management and teachers to break with the myth of racial democracy and the silencing or concealment about racism and racial discrimination that still underestimate and inferiorize the black difference. The research used documentary analysis, interviews, questionnaire and observations. The results of the research pointed out that these legislations require other paradigms to think about ethnic-racial difference and allow the break from the homogenizing and hegemonic vision of education.